Continental Fog Attenuation Empirical Relationship from Measured Visibility Data - Nadeem, F.; Javornik, T.; Leitgeb, E.; Kvicera, V.; Kandus, G. (Společnost pro radioelektronické inženýrství, 2010)
Free Space Optics (FSO) has the great potential for future communication applications. However, weather influenced reduced availability had been the main cause for its restricted growth. Among different weather influences fog plays the major role. A new model generalized for all FSO wavelengths, has been proposed for the prediction of continental fog attenuation using visibility data. The performance of the proposed model has been compared with well known models for measured attenuation data of Continental fog. The comparison has been performed in terms of Root Mean Square Error (RMSE).
Keywords: FSO; attenuation; simulation; fog; model comparison